Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations DEVONIAN ASSOCIATION FOR CRIPPLES' AID. J. CLINIC ACCOUNT. INCOME AND EXPENDITURE ACCOUNT FOR THE YEAR ENDED 31ST DECEMBER, 1932. EXPENDITURE. INCOME. £ s. d. £ s. d. £ s. d. £ s. d. TO SURGERY AND DISPENSARY. BY RECEIPTS ON ACCOUNT OF SERVICES RENDERED. Dressings 49 12 11 Drugs 41 17 8 (a) From Patients and other sources 297 19 5 Sundries 4 14 0 Appliances 416 1 4 (b) From Public Authorities 512 5 11 Devon County Council 1251 13 10 „ SALARIES. Exeter City Council 189 3 2 Medical 490 13 8 Torquay Education 165 4 11 Surgeon's Travelling Expenses 53 13 4 Cornwall Education 56 17 0 After-Care Sisters 245 17 7 Barnstaple Education 64 11 6 After-Care Sisters' Travelling Expenses 231 19 11½ Tiverton Education 44 6 6 1771 16 11 Miss Culross 2 8 0 (c) From Public Assistance Committees 14 0 11 1024 12 6½ „ UNIFORMS 7 12 0 „ X-RAY 175 8 0 „ VIOLET RAY 1 4 6 „ ADMINISTRATION. Postages and Sundries 102 19 11½ Printing and Stationery 27 11 11 Renewals 9 9 7 Clinic Travelling Expenses 13 1 3 Bank Charges 3 3 0 Interview Expenses 3 15 6 Ambulance 6 1 0 Transport 5 9 7 171 11 9½ „ ADDITIONAL EQUIPMENT 26 5 8 „ RENT — Clinic Accommodation 19 5 10 „ BALANCE, being Excess of Income over Expenditure for the year 145 11 0 £2,083 17 3 £2,083 17 3 We have examined the above Account with the Books, Vouchers and Records, and certify the same to be correct in accordance therewith. WARE, WARD & CO., Chartered Accountants, Auditors. Exeter. 27th February, 1933. 46 292/841.51/2/2